Exploring Low Reading Interest and Digital Literacy among Indonesian Pre-service Teachers: A Single-Case Study at a Private University in South Sulawesi - Sefrin Siang Tangkearung; Topanus Tulak; Andi Kaharuddin; Arshad SMBM (Jurusan Teknik Informatika dan Komputer, 2026)
Purpose – This study qualitatively investigates the causes of low reading interest among pre-service primary teachers at a private university in Indonesia and analyzes its implications for their digital literacy. Given the critical role of teachers in fostering literacy, understanding this issue is essential for developing effective educators. Design – Employing a single-case study design, data were collected through in-depth interviews, non-participant observations, and documentation with 12 pre-service teachers. Thematic analysis was used to identify patterns in participants' lived experiences. Findings – Results indicate that reading interest is primarily instrumental, driven by assignment completion rather than curiosity. Identified causes include low intrinsic motivation, a lack of supportive academic culture, and pervasive digital distractions. Consequently, this leads to passive technology use and weak critical filtering skills, evidenced by students' difficulty in evaluating source credibility and a tendency to prioritize superficial online content over in-depth analysis. Research Implications – As a single-site case study, the findings on academic culture may not be generalizable to all institutions. The study relies on self-reported data, which introduces potential for social desirability bias. Originality – The study concludes that effective digital literacy requires a strong foundation in conventional deep reading, necessitating an integrated literacy ecosystem in teacher education institutions. It offers a nuanced understanding of the mechanisms linking instrumental reading to poor digital outcomes.